Boronic acid derived salicylidenehydrazinopyridine (BOSPY) complexes with aggregation-induced emission for fluorescence imaging of cellular organelles. (February 2023) - Wang, Hua; Guo, Xing; Bu, Weibin; Kang, Zhengxin; Yu, Changjiang; Wu, Qinghua; Jiao, Lijuan; Hao, Erhong
Abstract: A series of boronic acid derived salicylidenehydrazinopyridine complexes have been synthesized from the condensation of 2-hydrazinopyridine or 2-hydrazinoquinoline and salicylaldehyde then followed by complexation with various boronic acids. Their X-ray structures demonstrate that the boron atoms adopt a tetrahedral geometry and the aryl substituents from arylboric acids along the vertical axis gave the molecule stereotactic structure and induced molecular chirality. These dyes have good solubility on organic solvents due to the nonplanar curved structure and the presence of axial-substituted groups that provide steric protection. They have strong visible-light absorption, weak emission and large Stoke shifts in organic solvents. Interestingly, molecular aggregates of these new boron complexes experienced the transformation from H -type aggregation to J- type aggregation and exhibited strong aggregation-induced emission (AIE) activities. These novel AIE dyes showed great potential as bioimaging dyes, and two complexes were mainly distributed in lipid droplets of cells in colocalization experiments. Graphical abstract: Image 1 Highlights: New boron complexed fluorophore (BOSPY ) has been developed from various arylboric acids. Molecular chirality of these dyes after boron complexation was confirmed by X-ray structures. These dyes exhibit strong aggregation-induced emission (AIE). These AIE dyes are suitable for fluorescence imaging and two dyes can specifically localize in lipid droplets of cells.